Promising outcomes of modified ALPPS for staged hepatectomy in cholangiocarcinoma - Mehrabi, Arianeb; Golriz, Mohammad; Ramouz, Ali; Khajeh, Elias; Hammad, Ahmed; Hackert, Thilo; Müller, Beat P.; Strobel, Oliver; Ali-Hasan-Al-Saegh, Sadeq; Ghamarnejad, Omid; Saeedi, Mohammed al; Springfeld, Christoph; et al. (Cancers, 2023)
Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) is a two-stage procedure that can potentially cure patients with large cholangiocarcinoma. The current study evaluates the impact of modifications on the outcomes of ALPPS in patients with cholangiocarcinoma. In this single-center study, a series of 30 consecutive patients with cholangiocarcinoma (22 extrahepatic and 8 intrahepatic) who underwent ALPPS between 2011 and 2021 was evaluated. The ALPPS procedure in our center was modified in 2016 by minimizing the first stage of the surgical procedure through biliary externalization after the first stage, antibiotic administration during the interstage phase, and performing biliary reconstructions during the second stage. The rate of postoperative major morbidity and 90-day mortality, as well as the one- and three-year disease-free and overall survival rates were calculated and compared between patients operated before and after 2016. The ALPPS risk score before the second stage of the procedure was lower in patients who were operated on after 2016 (before 2016: median 6.4; after 2016: median 4.4; p = 0.010). Major morbidity decreased from 42.9% before 2016 to 31.3% after 2016, and the 90-day mortality rate decreased from 35.7% before 2016 to 12.5% after 2016. The three-year survival rate increased from 40.8% before 2016 to 73.4% after 2016. Our modified ALPPS procedure improved perioperative and postoperative outcomes in patients with extrahepatic and intrahepatic cholangiocarcinoma. Minimizing the first step of the ALPPS procedure was key to these improvements.